MsCL-P1: A multifunctional C-type lectin from largemouth bass (Micropterus salmoides) with broad microbe binding and agglutination activities - Siyi She; Ying Ye; Fengyao Guo; Shun Yang; Mengmeng Huang; Hui Fei (Comparative Immunology Reports)
C-type lectins are a family of calcium-dependent carbohydrate-recognition domain (CRD) containing proteins that play a pivotal role in innate immunity. In this study, we characterized a novel C-type lectin, MsCL-P1, from the largemouth bass (Micropterus salmoides), an economically important fish species in aquaculture. MsCL-P1, a transmembrane protein with a CRD, was identified through liver transcriptome sequencing and further analyzed for its immune functions. The full-length cDNA of MsCL-P1 encodes a polypeptide of 789 amino acids, including one CRD, four coiled coil regions, and two collagen domains. Sequence analysis revealed high similarity among CRD domains from different species, suggesting conserved binding specificity. The recombinant CRD of MsCL-P1 (rCRD) demonstrated binding activity to various pathogen-associated molecular patterns (PAMPs), including lipopolysaccharide (LPS), peptidoglycan (PGN), and glucan (GLU), as determined by ELISA. Furthermore, the rCRD showed significant binding activity towards multiple microbes, including Gram-positive bacteria, Gram-negative bacteria, and fungi. Agglutination assays revealed that rCRD could agglutinate Aeromonas veronii and Saccharomyces cerevisiae, but not Micrococcus luteus. Carbohydrate binding specificity assays indicated that rCRD's agglutination activity could be suppressed by D-mannose and D-galactose. Lastly, antibacterial activity assays showed that rCRD inhibited the growth of M. luteus, E. coli, and A. veronii. These results suggest that MsCL-P1 plays a multifaceted role in the innate immune response of largemouth bass, potentially through recognition of PAMPs, agglutination of microbes, and direct inhibition of microbial growth. This study enhances our understanding of the immune mechanisms in largemouth bass and contributes to the broader knowledge of C-type lectin functions in fish species.